Typology and Characterization of Dairy Cattle Farms in Nepal - Dhungana, Jyoti; Gauchan, Devendra; Panta, Hari Krishna; Timsina, Krishna Prasad (Nepal Agriculture Research Journal, 2025)
The dairy sector plays a key role in generating income for smallholder farmers in Nepal.  However, dairy cattle farms have variations in production practices and farm types, and very few studies have been conducted to understand their diversities. Therefore, this study aims to assess the typologies and characteristics of dairy cattle farms.  Surveys were conducted across 407 dairy cattle farms in Ilam (86), Morang (114), Kavre (91), and Chitwan (116) between February and October 2024, representing the Hill and Terai regions of Nepal. Data was validated through 30 Key Informant Interviews (KIIs) and 10 Focus Group Discussions (FGDs). The Principal Component Analysis (PCA) and Cluster Analysis (CA) were used for data analysis, along with one-way ANOVA and Chi-square test for characterization. The PCA result indicated that farm area, forage area, technology, dairy cattle, and daily milk sales influenced the first component (42.38%), land holdings and feed rate affected the second component (11.39%), and lactation period, experience in dairy farming, and milk yield consisted third component (10.45%), collectively explaining 64.22% of the total variation. CA identified three distinct farm typologies. Cluster 1 (24.8%) included large-sized, specialized, and commercialized dairy farms, cluster 2 (36.6%) consisted of medium-sized, market-oriented farms, and Cluster 3 (38.6%) featured small-sized farms with limited resources and lower production. A variation among the respondent farms was attributed to milk yield, scale of production, intensity of production, degree of commercialization, and management practices. Therefore, the extension strategies need to be tailored based on the size, type, and characteristics of each cattle farm.